Assessing Motivation to Read. (December 2013) - Malloy, Jacquelynn A.; Marinak, Barbara A.; Gambrell, Linda B.; Mazzoni, Susan A.
Abstract For most classroom teachers, recognizing when students are engaged in literacy activities – and perhaps more glaringly, when they are not – is a process that is key to evaluating the potential success of the instruction being offered. Students who are engaged have their eyes on what they are doing, are ardently attending to the teacher's read aloud or in reflective repose as they read independently. Moreover, students who are motivated to participate in literacy instruction are on task, cognitively and strategically engaged with the material, and perhaps affectively responding to the activity as well. Therefore, the purpose of this article is to report on an updated and more reliable revision of the Motivation to Read Profile (MRP‐R) and to engage in a discussion of how periodic, class‐wide administration of the MRP‐R can inform practices to support motivating classroom contexts.